A case of emergency pancreatoduodenectomy for bleeding from the duodenal mucosa due to arteriovenous malformation of the pancreatic head. Issue 9 (21st September 2021) - Kitazono, Masaki; Fujita, Makoto; Katsue, Katsugi; Ikeda, Naotaka; Oyama, Tomohiro; Eguchi, Mayumi; Kamimura, Go; Sato, Rikiya; Uchiyama, Shuichiro; Toyosaki, Ryoichi; Suenaga, Toyokuni
Abstract: A rare case of bleeding from the duodenal mucosa due to arteriovenous malformation of the pancreatic head is reported. Caution needs to be observed, then excision may be necessary since noninvasive treatment such as coil embolization is not enough for complete hemostasis when patient suddenly decompensates. Abstract : A rare case of bleeding from the duodenal mucosa due to arteriovenous malformation of the pancreatic head is reported. Caution needs to be observed, then excision may be necessary since noninvasive treatment such as coil embolization is not enough for complete hemostasis when patient suddenly decompensates.